2017
DOI: 10.1149/07706.0085ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Engineering Semiconductor Interfaces Via Non-Native Nanostructures to Facilitate Electron-Hole Separation

Abstract: We modulate electron-hole separation at semiconductor junctions by stabilization of 'non-native' structures which are nanostructures whose discrete translational symmetry is different from that of the crystalline ground state. Four materials synthesis strategies involving click and colloidal chemistry are discussed and these methods can be potentially generalized to design a range of isomaterial and heteromaterial heterojunctions. The dynamics of electron-hole separation is demonstrated using density functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is found that C trap has a maximum close to the onset potential for δ-MnO 2 /Cd(OH) 2 , as reported earlier, while R ct,trap increases slightly, indicating not only that the current onset induces surface state charging/discharging but also that there are fewer holes in the trapped state, which lowers the activity. 82,83 For potentials more negative than the onset potential, C trap reduces after achieving a stable photocurrent. R trapping is essentially constant throughout the potential range, indicating that the charge transfer from bulk to interface states does not play a significant role in the conduction mechanism of the δ-MnO 2 /Cd(OH) 2 nanostructured electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is found that C trap has a maximum close to the onset potential for δ-MnO 2 /Cd(OH) 2 , as reported earlier, while R ct,trap increases slightly, indicating not only that the current onset induces surface state charging/discharging but also that there are fewer holes in the trapped state, which lowers the activity. 82,83 For potentials more negative than the onset potential, C trap reduces after achieving a stable photocurrent. R trapping is essentially constant throughout the potential range, indicating that the charge transfer from bulk to interface states does not play a significant role in the conduction mechanism of the δ-MnO 2 /Cd(OH) 2 nanostructured electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lattice‐mismatch leads to the lowering of the stability of hetero‐structure and promotes defect formation at the interface. However, the probability of formation of interfacial defects can be lowered by either (a) formation of heterostructures with different polymorphs of the same material as the variation in crystal structure might be gradual (F. Cao et al, 2016; Pala, 2020; Rashmi & Pala, 2019; Saha et al, 2017; P. Sun et al, 2013; Zhao, Zhu, Li, & Liu, 2015) or (b) through “click” chemistry between azide and alkyne functionalized particles wherein the intermediate five‐membered cyclic structure act as a conducting bridge of charge‐carriers between both of the heterostructure forming material (Behara et al, 2016; Upadhyay et al, 2013, 2016). The synthesis approaches for stabilization of native/non‐native semiconductor junctions have already been addressed in reviews and the interested reader is directed to them for further elaboration (Pala, 2020; Saha et al, 2017).…”
Section: Electrocatalytic and Photo‐electrocatalytic Reaction And Nonmentioning
confidence: 99%
“…Sun et al, 2013;Zhao, Zhu, Li, & Liu, 2015) or (b) through "click" chemistry between azide and alkyne functionalized particles wherein the intermediate five-membered cyclic structure act as a conducting bridge of charge-carriers between both of the heterostructure forming material Upadhyay et al, 2013Upadhyay et al, , 2016. The synthesis approaches for stabilization of native/non-native semiconductor junctions have already been addressed in reviews and the interested reader is directed to them for further elaboration (Pala, 2020;Saha et al, 2017).…”
Section: Photo-electrocatalytic Reaction and Non-native Polymorphmentioning
confidence: 99%
See 2 more Smart Citations